THE RELATIONSHIP BETWEEN BIMODAL LEARNING STYLES AND STUDENT'S LEARNING OUTCOMES IN WORK AND ENERGY TOPICS - Rusnayati, Heni; Putri, Wilda Oqctaria Neizar (Journal of Teaching and Learning Physics, 2022)
This study aims to obtain information about the relationship between bimodal learning styles and students' cognitive learning outcomes in work and energy. The bimodal learning style in this research focuses on the visual-auditory and visual-kinesthetic learning styles. The research method used is the correlational method. This research was conducted in one of the schools in Kuningan district, West Java, with a research sample of 65 students. Data were collected through questionnaires and instruments about business and energy materials. The results of the study found that there was no significant relationship between learning styles and learning outcomes. This can be seen from the calculation of the learning style correlation test with learning outcomes obtained p-value> 0.05. The implication of this research is to provide information about student learning style (V-A) and (V-K) profiles and student learning outcomes profiles, and the absence of a relationship between learning styles and student learning outcomes. This research also provides information to students about their learning styles and educators so that they can apply teaching styles and methods that can accommodate students' learning styles so that students can be more active in following the learning process.